A contribuiç\~ao dos ricos para a desigualdade de renda no Brasil - Marcos Hecksher; Pedro Luis do Nascimento Silva; Carlos Henrique Corseuil (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The share of the income inequality explained by the 10% richest members of the Brazilian population is higher than 50%. This percentage is higher in Brazil than what is found for the United States (45%), Germany (44%) and Great Britain (41%). Inequality was measured using an index which is still not much used in the socioeconomic literature, the J-divergence. It can be defined as the sum of Theil's T and L indices, but unlike these and the Gini index, the J-divergence of a population and its corresponding sample estimates can be easily decomposed as the sum of the individual contributions to the total inequality. Publicly available microdata on equivalised and per capita household total monthly income from the Brazilian National Household Sample Survey (PNAD) were used to estimate the J-divergence for each year from 1981 to 2015, and the corresponding shares of the inequality explained by each twentieth of the income distribution. In the period 2001-2014 of reduction of inequality in PNAD, the central group of the distribution reduces its share in J-divergence.
Keywords: D31; D63; 330; income inequality; decomposition; household sample survey